Liquid biopsy - a review - WERONIKA RUTKOWSKA-KAWALEC; Karolina Michalczuk; Dariusz Fabian; Marek Kurowski; Elżbieta Leszczyńska-Knaga; Natalia Jakubczyk; Paweł Moczydłowski; Monika Ryglewicz; Anna Gliwa; Karolina Kuczapska (Journal of Education, Health and Sport)
Introduction and objective: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related deaths worldwide. Early detection is crucial for better outcomes. Traditional diagnostic methods, such as imaging and biopsies, often fail to detect HCC in early stages. Liquid biopsy, based on circulating free DNA (cfDNA) analysis, offers a promising, non-invasive approach, allowing frequent testing, addressing tumor heterogeneity, and reducing costs.